A Study of the Reaction of N-Bromosuccinimide with Indomethacin - Singh, R.N.P.; Sinha, A.K.; Sinha, Niranjan (Asian Journal of Chemistry, 2010)
The reaction of N-bromosuccinimide with indomethacin in acid mediumhas been studied. The purified product has been identified by TLC, elementalanalysis and infra-red studies, and a reaction mechanism is proposedon the basis of the results. The reaction proceeds smoothly and consistentlyand can be studied kinetically so as to determine various thermodynamicparameters.